2012
DOI: 10.1007/s12040-012-0173-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a perfect prognosis probabilistic model for prediction of lightning over south-east India

Abstract: A prediction model based on the perfect prognosis method was developed to predict the probability of lightning and probable time of its occurrence over the southeast Indian region. In the perfect prognosis method, statistical relationships are established using past observed data. For real time applications, the predictors are derived from a numerical weather prediction model. In the present study, we have developed the statistical model based on Binary Logistic Regression technique. For developing the statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…By observing the variations of the composite time series of these thermodynamic indices, it is possible to explain the prerequisites necessary for the genesis of thunderstorm activity. In the recent study by [ Rajeevan et al ., ], a prediction scheme is developed to nowcast the probability of lightning over southeast India using various thermodynamical indices which explain the tropospheric instability. From the study it is inferred that the above mentioned eight parameters showed appreciable differences in threshold for the occurrence of thunderstorm and nonthunderstorm cases, 60% or more storms are formed when KI exceeds 42°C, MEANRH 950‐850hPa raises more than 75%, and PW value reaches more than 5.4 cm.…”
Section: Superepoch Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…By observing the variations of the composite time series of these thermodynamic indices, it is possible to explain the prerequisites necessary for the genesis of thunderstorm activity. In the recent study by [ Rajeevan et al ., ], a prediction scheme is developed to nowcast the probability of lightning over southeast India using various thermodynamical indices which explain the tropospheric instability. From the study it is inferred that the above mentioned eight parameters showed appreciable differences in threshold for the occurrence of thunderstorm and nonthunderstorm cases, 60% or more storms are formed when KI exceeds 42°C, MEANRH 950‐850hPa raises more than 75%, and PW value reaches more than 5.4 cm.…”
Section: Superepoch Analysismentioning
confidence: 99%
“…During the recent years, a variety of statistical techniques have been used to develop forecast models for thunderstorms and lightning [Reap, 1994;Lambert et al, 2005;Shafer and Fuelberg, 2006]. In a recent study by Rajeevan et al [2012], a statistical model based on binary logistic regression was developed for predicting probability of lightning occurrence over southeast India using the perfect prognostic method (PPM). For real time forecasts, predictors are derived from 12 h predictions using the WRF model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several statistical models that allow prediction of the occurrence of a lightning day: classification and regression tree (CART) techniques (Burrows et al , ), neural networks and fuzzy logic (Kuk et al , ) and binary logistic regression (Mazany et al , ; Lambert et al , ; Shafer and Fuelberg, , ; Rajeevan et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…) were also developed to forecast thunderstorm. Rajeevan et al (2012) developed a statistical model based on binary logistic regression for predicting the probability of lightning occurrence over southeast India using the perfect prognostic method (PPM). Though many studies were carried out using various techniques/observations, the prediction of severe convective events is still a difficult process which may be mainly because of (i) lack of observations of the initial state or (ii) relative coarse resolution.…”
Section: Introductionmentioning
confidence: 99%